Almost sure functional central limit theorems for multiparameter stochastic processes - Czerebak-Morozowicz, E.B.; Rychlik, Z.; Urbanek, M. (Condensed Matter Physics, 2008)
We present almost sure central limit theorems for stochastic processes whose time parameter ranges over the d-dimensional unit cube. Our purpose here is to generalize the classic functional central limit theorem of Prokhorov (1956) for such processes. We prove multidimensional analogues of Glivenko-Cantelli type theorems.